Performance Optimization of DOA Estimation in Non-Uniform Linear Antenna Array by PSO Algorithm - Wan, Liang Tian; Si, Wei Jian; Han, Hui Lian (Applied Mechanics and Materials, 2014)
In order to estimate the coherent source, a modified multiple signal classification (MUSIC) algorithm is introduced. And a novel arrangement method for the non-uniform linear array by particle swarm optimization (PSO) algorithm is proposed. This method needs merely a signal source whose direction-of-arrival (DOA) has been exactly known. The proposed method has a simple processing and a strong stabilization. It could be applied to optimized arbitrary array configuration. The simulation verifies that the performance of DOA estimation is improved effectively, which has proved the validity of the proposed method.